Sistem Pendistribusian Air Bersih Metode Prabayar Terkendali Mikrokontroler Berbasis IoT - Efrizon; Muhammad Irmansyah; Anggara Nasution; Era Madona; Anggi Lifya Rani (Ikatan Ahli Informatika Indonesia (IAII), 2021)
A number of problems sometimes often arise regarding the flow of clean water from Regional Drinking Water Companies (PDAMs) to customers, such as the flow of water stops suddenly or there is no water at all, so it is necessary to manufacture a prototype system for monitoring the distribution of clean water with a microcontroller-controlled prepaid method. IoT based. The distribution of PDAM water that is channeled to consumers can be monitored online through the Internet network. The objectives of this research are (a) to make a prototype (prototype) of a prepaid clean water distribution system controlled by a microcontroller based on IoT, (b) to program an Arduino IDE-assisted system, and (c) to measure system performance. The research method starts from making a prototype physical form of clean water distribution assisted by a microcontroller, programming the microcontroller and Wi-Fi module, and measuring system performance. The results of measuring system performance are indicated by an error in the ultrasonic sensor reading HC-SR04 that occurs when the water level is low and too high with a maximum measured water level of 95%. The error when measuring the waterflow sensor at the water level is lower than 49% which is influenced by the water speed from the low pressure pump when the water level is below that value. The accuracy level of the waterflow sensor is 96.96% which is based on the sensor measurement results which are compared to the measurement results with a measuring cup. The system can monitor data readings from the waterflow sensor by using the NodeMCU ESP8266 on a web server from Thinkspeak via the smartphone screen. Overall the tool can function well